Diferensiasi Model Pembelajaran Guru Pendidikan Aagama Islam di Madrasah Tsanawiyah Negeri 1 Bangka Tengah - Sari, Nila Siska; Syarifah HR DG Tujuh; Rudini; Karyono; Deka Sulastri (JUPIN (Jurnal Pendidikan Islam Nusantara), 2025)
In Madrasah teachers predominantly apply a teacher-centred learning model. Even though students currently growing up in the digital era certainly like interactive, technology-based and factual learning. Innovative and adaptive learning models can bring great benefits to students in terms of intellectual development, skills and output. The aim of the research is to analyze the differentiation in the use of PAI teacher learning models at MTsN 1 Central Bangka. This research includes qualitative research. Data was obtained through semi-structured interviews, observation and documentation. The informants were 6 PAI teachers at MTsN 1 Central Bangka. The results of the research found that the use of learning models by six PAI teachers at MTsN 1 Central Bangka could be divided into three learning models. Firstly, there are 4 groups of PAI teachers who mostly use direct learning models. The two groups that used the problem-based learning model consisted of 1 person. The three groups that use the cooperative learning model consist of 1 person. This research can contribute to PAI teachers implementing student-centered learning models that are innovative, varied and adaptive according to educational subjects and learning materials in class. This research can explore the ability of PAI teachers to develop innovative and adaptive learning models that can help students meet their learning needs both in terms of output, motivation and certain skills.